Madinah sebagai Cikal Bakal Negara Berbasis Good Governance - Dikdik Dahlan Lukman (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
After the hijrah from Makkah to Medina in 622 AD, Rasulullah SAW built a society that astonished the world at that time. His leadership was not only able to create social and political stability, but also had an impact on the existence of two major world powers, namely the Byzantine Empire and the Persian Sassanid Dynasty. This research aims to examine the governance of the Prophet Muhammad in Medina with two main focuses: (1) whether the community of Medina at that time could be categorized as a state, and (2) whether the principles of good governance had been applied in the leadership of the Prophet Muhammad. This research uses a qualitative approach with a case study method, which is supported by historical and normative literature studies from primary and secondary sources such as the Qur'an, Hadith, and classical and modern literature. The results showed that the Medina community during the time of the Prophet Muhammad had fulfilled the main elements of a state, namely territory, people, government, binding law, and recognition from other parties. In addition, the Prophet's governance has reflected the principles of good governance, including: community participation, law enforcement, transparency, justice, equality, efficiency, accountability, responsiveness, and strategic vision. The discussion further emphasized that the specialty of the Prophet's government lies in its spiritual foundation, namely divine revelation (Al-Qur'an) and sunnah as the main guidelines. His leadership was not only administrative-political, but also moral and ethical. His legal system emphasized justice, equal rights, and individual and collective responsibility before God. The practice of professionalism, accountability, and transparency is evident in public policies and the implementation of government administration. The government of the Prophet Muhammad in Medina can be used as an ideal model of governance that upholds moral and human values.